Transformasi Positif: Analisis Sistem Jual Beli Online di Anisa Online Shop Grosir Mlorah Rejoso Nganjuk dalam Perspektif Ekonomi Islam - Bhaswarendra Guntur Hendratri; Alfin Yuli Dianto; Mas'ut Mas'ut; Mukhamad Zakariya; Mohamad Fuad Udin (Journal on Education, 2023)
In Islamic economics, there are muamalah activities, such as buying and selling, leasing, and lending, regulated by religion for the common good. These rules ensure that human life is secure and organized without harmful deviations. This research focuses on the online buying and selling system at Anisa Online Shop Grosir in Mlorah Village, Rejoso Sub-district, Nganjuk Regency, and its impact on customers, as well as the Islamic economic perspective. The research objectives encompass understanding the online buying and selling system, its impact on customer satisfaction, and the Islamic economic perspective on this system. The research method employs a qualitative approach with the researcher as the main instrument. The findings reveal that the online buying and selling system at Anisa Online Shop Grosir involves retail and wholesale purchases, positively impacting customer satisfaction, and aligning with Islamic Sharia without violations.